Pengaruh Sikap Keuangan Dan Pengetahuan Keuangan Terhadap Pengelolaan Keuangan Dengan Kepuasan Keuangan Sebagai Variabel Intervening Pada Mahasiswa Di Kota Medan - Inayah Salsabilah Gultom; Qahfi Romula Siregar (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
This study aims to find out how the influence of Financial Attitude and Financial Knowledge on Financial Behavior with Financial Satisfaction as Intervening Variables in Students in Medan City. The method used in this study is to use an associative and quantitative approach. The population in this study were all students who were in the city of Medan and the sample was 100 people. The research instrument was in the form of a test. Data collection tools were used. Data collection tools used were interviews, documentation studies, and questionnaires.